Analisis Kandungan Asam Lemak Ikan Sidat (Anguilla Bicolor) Asal Danau Poso - Yulvani Toiba; Sri Mulyani Sabang; Tahril Tahril; Sitti Aminah (Media Eksakta, 2022)
Analysis of Fatty Acid Content of Eel (Anguilla Bicolor) from Lake Poso. Skipsi, Chemistry Education Study Program, Department of Mathematics and Natural Sciences Education, Tadulako University, Palu. Advisor Sri Mulyani Sabang. The purpose of this study was to determine the fatty acid content of eel (Anguilla Bicolor) originating from Lake Poso. The method used to analyze the fat content was the shoxletation extraction method. The results showed that the fat content of eel (Anguilla Bicolor) from Lake Poso = 1.94%. Meanwhile, to determine the fatty acid composition of eel, it was analyzed using gas chromatography with the composition of fatty acids found in eel (Anguilla Bicolor) including saturated fatty acids 51.89%, monounsaturated fatty acids = 42.68%, and unsaturated fatty acids. plural saturation = 7.99%. Eel has many benefits for the human body, eel meat is rich in protein, vitamins, fatty acids, and micro elements (minerals). The content of vitamins in eels include vitamin A, vitamin B1, and vitamin B2, as well as micro elements such as Zn (Zink). In addition to vitamins and micro elements, eels also contain unsaturated weak acids needed by the body, including omega fatty acids which are useful for the development of children's brain cells.